The Theory of Mind and Socialization, Communication and Living Skills of Students with Intellectual Disability - Mahdi Abdollah-Zadeh; Narges Adib-Sereshki; Ma'soumeh Pourmohammadreza-Tajrishi; Enayatollah Bakhshi (University of Social Welfare and Rehabilitation Sciences, 2012)
Objective: The purpose of this study is to investigate the relationship between Theory of mind and socialization, communication and living skills (adaptive behaviors) in students with intellectual disability. Materials & Methods: This study that took place with a correlation method including 60 students with intellectual disability (30 boys and 30 girls). In order to collect the data for theory of mind, 38-item TOM test were used. Data of socialization, communication and living skills was gathered by Vinland Adaptive Behavior Scale. Results: Correlation between level 2 of theory of mind and socialization was significant (P=0.005) but there were not a significant correlation between the levels of theory of mind and communication and living skills (P>0.05). Conclusion: When the conception of primary false belief (level 2 in theory of mind) increases, the scores for socialization skills increases too.